2013
DOI: 10.1001/jamaneurol.2013.3475
|View full text |Cite
|
Sign up to set email alerts
|

Similarity of Lateralized Rhythmic Delta Activity to Periodic Lateralized Epileptiform Discharges in Critically Ill Patients

Abstract: The increasing use of continuous electroencephalography (EEG) monitoring in the intensive care unit has led to recognition of new EEG patterns that are of unclear or unknown significance.OBJECTIVE To describe an EEG pattern, lateralized rhythmic delta activity (LRDA), encountered in critically ill subjects and determine its clinical significance in this setting. DESIGN, SETTING, AND PARTICIPANTSRetrospective review at an academic medical center of EEG recordings, medical records, and imaging studies of critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
131
3
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 80 publications
(139 citation statements)
references
References 27 publications
3
131
3
2
Order By: Relevance
“…As rhythmic delta activity represented only a small proportion of the PP observed in our study, it is hard to draw firm conclusions regarding its association with IED. However, in a recent study, Gaspard et al [4] showed a strong association of lateralized rhythmic delta activity with lateralized periodic discharges and the occurrence of seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As rhythmic delta activity represented only a small proportion of the PP observed in our study, it is hard to draw firm conclusions regarding its association with IED. However, in a recent study, Gaspard et al [4] showed a strong association of lateralized rhythmic delta activity with lateralized periodic discharges and the occurrence of seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Their clinical and prognostic significance is largely unknown. Spikes, sharp waves, and periodic patterns (PP) such as periodic lateralized discharges and rhythmic delta have been linked to an increased risk of seizures in ischemic stroke [3,4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…The objectives of this project were to create a database (1) to serve as a repository of research data to facilitate multicenter studies and (2) to serve as a clinical tool that could be integrated into daily workflow for standardized reporting of cEEG monitoring results at member sites. Multicenter collaborative intensive care unit EEG collaboration is required to study relatively rare conditions and has resulted in key clinical findings in the field of cEEG (Gaspard et al, 2013a, 2013b; Kilbride et al, 2013; Schmitt et al, 2012). …”
mentioning
confidence: 99%
“…Substantial efforts have been made to standardize critical care EEG terminology and to associate EEG patterns with clinical course and outcome. [1][2][3][4][5] One of the main indications for CEEG is to detect electrographic seizures. Most electroencephalographers use a definition of seizures that includes a minimal duration of 10 seconds, [2][3][4][5][6][7] which reflects the typical duration of partial seizures in patients with chronic epilepsy.…”
mentioning
confidence: 99%